1967
DOI: 10.1161/01.cir.35.4.734
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Body Weight to Development of Coronary Heart Disease

Abstract: Interrelationships between weight change, serum cholesterol, blood pressure levels, and the risk of developing coronary heart disease have been explored in 5,127 men and women who have been followed over 12 years for signs of initial development of coronary heart disease. Antecedent relative weight and weight gain after age 25 years proved to be strongly related to risk of angina pectoris and sudden death but were unassociated with development of myocardial infarction. An excess risk of angina pectoris and sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
8

Year Published

1970
1970
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(61 citation statements)
references
References 23 publications
4
47
2
8
Order By: Relevance
“…9 All the atherogenic effects of obesity, however, may not be through known risk factors; several epidemiological studies suggest that excess body weight is an "independent" risk factor. 40 " 45 The results reported here may partially account for this claim. Art increased turnover of apoLDL itself may be a risk factor for CHD.…”
Section: Obesity Apoldl Metabolism and Coronary Heart Diseasesupporting
confidence: 55%
“…9 All the atherogenic effects of obesity, however, may not be through known risk factors; several epidemiological studies suggest that excess body weight is an "independent" risk factor. 40 " 45 The results reported here may partially account for this claim. Art increased turnover of apoLDL itself may be a risk factor for CHD.…”
Section: Obesity Apoldl Metabolism and Coronary Heart Diseasesupporting
confidence: 55%
“…A longitudinal study, performed in the city of Framingham 41 , showed the association of obesity with morbimortality due to cardiovascular disease in both sexes and different age ranges. The coexistence of disorders as dyslipidemia, diabetes mellitus and hypertension, made impossible to identify the obesity as an isolated risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…No presente, é universalmente aceito que obesidade é um fator de risco independente para doença cardíaca isquêmica (12,15,96), principalmente quando associada a acúmulo visceral de gordura, que está presente em 90% dos pacientes obesos com coronariopatia (106). O ganho de peso durante a vida adulta aumenta o risco de doença coronariana e mortalidade em ambos os sexos, independentemente da presença de outros fatores de risco cardiovascular clássicos, sugerindo-se a implicação da hiperinsulinemia no fenômeno trombogênico.…”
Section: Doença Cardíaca Isquêmica Doença Cardíaca Isquêmicaunclassified